GOVERNING INTERESTS OF FULANI HERDSMEN AND PEASANT FARMERS IN NATURAL RESOURCES IN THE ASANTE AKIM NORTH DISTRICT OF GHANA - Mensah, John Victor; Adamtey, Ronald; Abdulai, Abdul-Rahim (Advances in Social Sciences Research Journal, 2016)
This study examined the governance of interests of Fulani cattle herdsmen and peasant farmers in land, water and pastures of the Asante Akim North District of Ghana. Using stakeholder interviews with key officers of the Asante Akim North District Assembly (AANDA), senior officers of District Police Service, key persons in the Traditional Council, cattle owners and focus group discussion sessions with farmer groups and groups of herders, the study revealed that conflicting interests among stakeholders have led to violent conflicts between the herdsmen and peasant farmers. It is recommended that stakeholder governance should employ a platform that provides equal opportunity to herders and farmers to raise their concerns, negotiate and find a solution for peaceful coexistence as well as enforcement of the rule of law in the area.